The interaction between dietary nitrates/nitrites intake and gut microbial metabolites on metabolic syndrome: a cross-sectional study - Mirzababaei, Atieh; Mahmoodi, Maryam; Keshtkar, Abbasali; Ebrahimi, Sara; Pashayee-Khamene, Fereshteh; Abaj, Faezeh; Radmehr, Mina; Khalili, Pardis; Mehri Hajmir, Mahya; Mirzaei, Khadijeh (Frontiers in Public Health, 2024)
Background Metabolic syndrome (MetS) prevalence has increased globally.The evidence shows thatdiet and gut microbial metabolites includingtrimethylamine N-oxide (TMAO) and kynurenine (KYN) play an important role in developing MetS. However, there is a lack of evidence on associations between between diet and these metabolites. This study aimed to investigate the interaction between dietary nitrate/nitrite and gut microbial metabolites (TMAO, KYN) on MetS and its components. Methods This cross-sectional study included 250 adults aged 20–50 years. Dietary intake was assessed using food frequency questionnaires (FFQ), and serum TMAO and KYN levels were measured. MetS was defined usingthe National Cholesterol Education Program Adult Treatment Panel (NCEP ATP III) criteria. Result The ATPIII index revealed an 11% prevalence of metabolic syndrome among the study participants. After adjusting for confounders, significant positive interactions were found: High animal-source nitrate intake and high TMAO levels with elevated triglycerides (TG) (p interaction = 0.07) and abdominal obesity (p interaction = 0.08). High animal-source nitrate intake and high KYN levels with increased TG (p interaction = 0.01) and decreased high-density lipoprotein cholesterol (HDL) (p interaction = 0.01).Individuals with high animal-source nitrite intake and high TMAO levels showed increased risk of hypertriglyceridemia (OR: 1.57, 95%CI: 0.35–2.87, p = 0.05), hypertension (OR: 1.53, 95%CI: 0.33–2.58, p = 0.06), and lower HDL (OR: 1.96, 95%CI: 0.42–2.03, p = 0.04). Similarly, high animal-source nitrite intake with high KYN levels showed lower HDL (OR: 2.44, 95%CI: 1.92–3.89, p = 0.07) and increased risk of hypertension (OR: 2.17,95%CI: 1.69–3.40, p = 0.05). Conversely, Negative interactions were found between high plant-source nitrate/nitrite intake with high KYN and TMAO levels on MetS and some components. Conclusion There is an interaction between dietary nitrate/nitrite source (animal vs. plant) and gut microbial metabolites (TMAO and KYN) on the risk of of MetS and its components. These findings highlight the importance of considering diet, gut microbiome metabolites, and their interactions in MetS risk assessment.